Study of Splenic Notches and Fissures in Bangladeshi Cadaver (Journal of Armed Forces Medical College, Bangladesh, 2026)
Background: Splenic notches are important landmark for the clinician to differentiate enlarged spleen from left kidney during abdominal palpation. Notches are usually present in the upper/superior border of spleen which represents the lobulated development from the left wall of dorsal mesogastrium and fuses with progress of age.Objective: To find out the incidence, position, number of splenic notches and fissure in Bangladeshi cadaver.Methods: This descriptive cross sectional study was done from July 2007 to June 2008 on 120 formalin fixed cadaveric human spleens in the department of Anatomy at Mymensingh Medical College, Mymensingh.Results: : In the present study, splenic notches were found in 85% of cases. In relation to sex the notches were found in 86.2% of male and 81.81% of female cadaver. In upper border notches were found in 84% of cases which were 1-7 in number. In lower border notches were present in 36.67% of spleens and are 1-3 in number. Spleenic fissure was found in 9.19% of male and 9.09% of female spleen.Conclusion: Adequate knowledge of splenic morphology will be helpful for the clinical diagnosis of splenic disease.JAFMC Bangladesh, Vol 21, No 1 (June) 2025: 12-15